Multifunctional electrocatalysts of nickel boride nanoparticles for superior hydrogen oxidation and water splitting. (December 2021) - Song, Fuzhan; Zhang, Tong; Qian, Yuqin; Shaw, Jeremy; Chen, Shutang; Chen, Gugang; Sun, Yujie; Rao, Yi
Abstract: The development of active, durable, and earth-abundant multifunctional electrocatalysts is of importance for hydrogen energy conversion and storage. Here, we report a facile strategy to synthesize earth-abundant nickel boride nanoparticles supported on reduced graphene oxide (Ni3 B/rGO) as multifunctional electrocatalysts for both hydrogen oxidation reaction and overall water splitting. The Ni3 B/rGO catalysts produce a hydrogen oxidation reaction current density of 2.39 mA cm −2 at an overpotential of 100 mV vs. reversible hydrogen electrode, being comparable to commercial Pt/C (2.95 mA cm −2 ) and 60 times as high as bare Ni/rGO (0.04 mA cm −2 ). In addition, the Ni3 B/rGO-based alkali electrolyzer affords 100 mA cm −2 at a cell voltage input of 1.85 V for electrocatalytic overall water splitting. Density functional theory calculations further demonstrate that the Ni3 B/rGO catalysts possess optimal adsorption energies of both H∗ and OH∗ intermediates, which are favorable to electrocatalytic hydrogen electrochemistry in an alkaline medium. This work opens a new avenue toward the rational design of high-performance platinum group metal-free multifunctional electrocatalysts for the hydrogen economy. Graphical abstract: Image 1 Highlights: The novel nickel boride nanoparticles/reduced graphene oxide was synthesized for hydrogen oxidation and water splitting. The obtained nickel boride nanoparticles/reduced graphene oxide catalysts exhibit a recording hydrogen oxidation reaction/hydrogen evolution reaction catalytic property. The water electrolyzer with high performance is also assembled.